Recovery following a marathon: a comparison of cold water immersion, whole body cryotherapy and a placebo control - Wilson, L. J.; Cockburn, E.; Paice, K.; Sinclair, S.; Faki, T.; Hills, F. A.; Gondek, M. B.; Wood, A.; Dimitriou, L. (European Journal of Applied Physiology, 2018)
Purpose: Cryotherapy is an increasingly popular recovery strategy used in an attempt to attenuate the negative impact of strenuous physical activity on subsequent exercise. Therefore, this study aimed to assess the effects of whole body cryotherapy (WBC) and cold water immersion (CWI) on markers of recovery following a marathon. Methods: Thirty-one endurance trained males completed a marathon. Participants were randomly assigned to a CWI, WBC or placebo group. Perceptions of muscle soreness, training stress and markers of muscle function were recorded before the marathon and at 24 and 48 h post exercise. Blood samples were taken at baseline, post intervention and 24 and 48 h post intervention to assess inflammation and muscle damage. Results: WBC had a harmful effect on muscle function compared to CWI post marathon. WBC positively influenced perceptions of training stress compared to CWI. With the exception of C-reactive protein (CRP) at 24 and 48 h, neither cryotherapy intervention positively influenced blood borne markers of inflammation or structural damage compared to placebo. Conclusion: The findings show WBC has a negative impact on muscle function, perceptions of soreness and a number of blood parameters compared to CWI, contradicting the suggestion that WBC may be a superior recovery strategy. Further, cryotherapy is no more effective than a placebo intervention at improving functional recovery or perceptions of training stress following a marathon. These findings lend further evidence to suggest that treatment belief and the placebo effect may be largely responsible for the beneficial effects of cryotherapy on recovery following a marathon.